A case study of the start in flat water kayaking competitions - Espinosa, M. (ISBS Proceedings Archive (Michigan), 2017)
The aim of this study was to investigate the relationship between shoulder and elbow coordination at the start of a flat-water kayaking competition. A high performance male competitor is analyzed based on the four main corporal positions and phases that the body adopts during a paddling cycle. Photogrammetric procedures were used with data extracted from the movements registered by three video cameras. The amplitude of the 3D angular displacement at the shoulders and elbows was calculated. Non-parametric statistical tests were applied to analyze the angular displacement in the phases of the stroke cycle. Results showed that there are significant differences between angular displacements due to the first stroke kinematic characteristics, but left and right shoulder - elbow are highly correlated. The movements performed in the stroke cycle visually reflect bilateral asymmetries.